2021
DOI: 10.3390/cells10112977
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Regulation of Ciliary Disassembly

Abstract: The primary cilium, an antenna-like structure that protrudes out from the cell surface, is present in most cell types. It is a microtubule-based organelle that serves as a mega-signaling center and is important for sensing biochemical and mechanical signals to carry out various cellular processes such as proliferation, migration, differentiation, and many others. At any given time, cilia length is determined by a dynamic balance of cilia assembly and disassembly processes. Abnormally short or long cilia can ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 119 publications
0
18
0
Order By: Relevance
“…24 Defective Rhodopsin trafficking is considered a common feature of RD in multiple ciliopathy models; moreover, in BBS animal models, endoplasmic reticulum stress response has been described. 25…”
Section: Retinal Dystrophymentioning
confidence: 99%
“…24 Defective Rhodopsin trafficking is considered a common feature of RD in multiple ciliopathy models; moreover, in BBS animal models, endoplasmic reticulum stress response has been described. 25…”
Section: Retinal Dystrophymentioning
confidence: 99%
“…This creates a protrusion, which ultimately becomes a cilium. As the cell reenters the cell cycle, the cilium will disassemble either through shedding or through axonemal disassembly before entering cell division (Patel & Tsiokas, 2021).…”
Section: Introduction Cell Division and Ciliogenesis Alternately Use ...mentioning
confidence: 99%
“…Considering that AURKA plays a key role in ciliary disassembly, and GBM cells constantly assemble and disassemble their cilia while proliferating, it was surprising to not observe increased GBM cilia frequency after Alisertib treatment. It is possible that AURKA inhibition in GBM cells stimulates activity of other molecules that promote ciliary disassembly such as HDAC6, NEK and others (for review see: (22, 35, 36)). However, we previously reported that overexpression of HDAC6 in our L0 or S7 glioma cells did not reduce cilia frequency or length (32).…”
Section: Discussionmentioning
confidence: 99%